The Politics of Housing in (Post-)Colonial Africa Accommodating Workers and Urban Residents - Barker-Ciganikova, Martina; Rüther, Kirsten; Waldburger, Daniela; Bodenstein, Carl-Philipp (African Minds, 2020)
Housing matters, no matter when or where. This volume of collected essays on housing in colonial and postcolonial Africa seeks to elaborate how and why housing is much more than an everyday practice. The politics of housing unfold in disparate dimensions of time, space and agency. Depending on context, they acquire diverse, often ambivalent, meanings. Housing can be a promise, an unfulfilled dream, a tool of self- and class-assertion, a negotiation process, or a means to achieve other ends. This volume analyzes housing in its multifacetedness, be it a lens to offer insights into complex processes that shape societies; be it a tool of empire to exercise control over private relations of inhabitants; or be it a means to create good, obedient and productive citizens. Contributions to this volume range from the field of history, to architecture and urban planning, African studies, linguistics, and literature. The individual case studies home in on specific aspects and dimensions of housing and seek to bring them into dialogue with each other. By doing so, the volume aims to add to the debate on studying urban practices and their significance for current social change.